2022
DOI: 10.1039/d2fo00143h
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic perturbations and health impact from exposure to a combination of multiple harmful Maillard reaction products on Sprague-Dawley rats

Abstract: The present study aimed to investigate the metabolic perturbations and health impacts of the co-accumulation of Maillard reaction products (MRPs), including acrylamide, harmane, and Nε-(carboxymethyl)lysine (CML), via serum biochemical and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…1E). Although our previous study showed that intake of harmane alleviated abnormal blood glucose metabolism caused by exposure to acrylamide, 19,20 the results of the present study showed that the intake of exogenous harmane did not play a positive role in the insulin resistance and abnormal blood glucose metabolism in GK rats.…”
Section: Resultscontrasting
confidence: 90%
See 3 more Smart Citations
“…1E). Although our previous study showed that intake of harmane alleviated abnormal blood glucose metabolism caused by exposure to acrylamide, 19,20 the results of the present study showed that the intake of exogenous harmane did not play a positive role in the insulin resistance and abnormal blood glucose metabolism in GK rats.…”
Section: Resultscontrasting
confidence: 90%
“…The doses of harmane in this study were selected based on the concentration of harmane in various foodstuffs, 6,12,23 with reference to the experimental doses employed in our previous studies and by other researchers. 19 Moreover, owing to the exposure time and interspecies and intraspecies differences, as shown in previous studies, 24 the safety and uncertainty factors of this chemical were chosen to compensate for human exposure and convert it to an appropriate rat dose that is comparable to human exposures from a daily diet high in β-carboline HA levels.…”
Section: Test Design and Animal Handlingmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, most studies used heat‐treated foods for feeding mice to study the effects of dietary AGEs intake on organismal health (Luo, Li, et al, 2022; Roncero‐Ramos et al, 2013). However, extensive heat processing foods contain various antinutritional and toxic compounds derived from the Maillard reaction (e.g., acrylamide [Quan et al, 2022], heterocyclic aromatic amines [Dong et al, 2020], and 5‐hydroxymethylfurfural [Han et al, 2019; Pérez‐Burillo et al, 2019]). Notably, Pouillart et al (2010) confirmed that the content of acrylamide and 5‐hydroxymethylfurfural were significantly higher in heat‐treated foods which had high AGEs content.…”
Section: Introductionmentioning
confidence: 99%